2000
DOI: 10.1179/135100000101535492
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate (DCA) reduces brain lactate but increases brain glutamine in experimental cerebral malaria: a1H-NMR study

Abstract: Recent findings that levels of brain lactate and alanine were elevated in murine cerebral malaria led us to investigate the effect of dichloroacetate (DCA; 60 mg/kg), an activator of pyruvate dehydrogenase, on the levels of brain metabolites, and on the survival of mice infected with Plasmodium berghei ANKA which normally causes lethal cerebral malaria. DCA significantly reduced brain lactate and alanine levels when administered to infected mice, had no effect on the TCA cycle-related metabolites glutamate, GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…SNO-pdhb enhances enzyme activity. The pyruvate dehydrogenase activator DCA has been used against CM and observed to reduce metabolic acidosis in the brain and reduce mortality. , When cells are stimulated by factors, ER stress occurs . ER morphology and function balance was destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…SNO-pdhb enhances enzyme activity. The pyruvate dehydrogenase activator DCA has been used against CM and observed to reduce metabolic acidosis in the brain and reduce mortality. , When cells are stimulated by factors, ER stress occurs . ER morphology and function balance was destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…A large study of Ghanaian children with malaria associated hyperlactataemia (n=124) showed no pharmacokinetic interaction between quinine and DCA and no unexpected adverse events with DCA when administered as a single 10-min infusion of 50 ml/kg body weight . DCA has been shown to improve outcome in a P. berghei infected rodent model of malaria and magnetic resonance imaging studies in P. berghei infected mice showed lower brain lactate levels in animals that received DCA (Rae et al 2000).…”
Section: Dichloroacetatementioning
confidence: 97%
“…A large study of Ghanaian children with malaria associated lactic acidosis (n=124) showed no pharmacokinetic interaction between quinine and DCA [68] and no unexpected adverse events with DCA. DCA improves outcome in a P. berghei-infected rodent model of malaria [106] and MRI studies on P. berghei infected mice show DCA lowers brain lactate levels [107]. most sensitive to the effects of hypoglycaemia.…”
Section: N-acetyl Cysteinementioning
confidence: 99%